2015
DOI: 10.1021/ct5010966
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of 441 Two-Residue Peptides in Aqueous Solution: Conformational Preferences and Neighboring Residue Effects with the Amber ff99SB-ildn-NMR Force Field

Abstract: Understanding the intrinsic conformational preferences of amino acids and the extent to which they are modulated by neighboring residues is a key issue for developing predictive models of protein folding and stability. Here we present the results of 441 independent explicit-solvent MD simulations of all possible two-residue peptides that contain the 20 standard amino acids with histidine modeled in both its neutral and protonated states. 3Jhnhα coupling constants and δhα chemical shifts calculated from the MD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…20e Water was modeled explicitly using the TIP4P-Ew model; 24 we selected this model for use in simulations because one of our long-term goals is to study protein-DNA interactions and the combination of the AMBER protein force field with the TIP4P-Ew water model is established as one of the best currently available for modeling peptide systems. 25 Na + and Cl − ions – which were added to 150 mM concentrations in order to crudely mimic physiological concentrations – were modeled using the appropriate set of parameters derived by Joung & Cheatham; 26 for simulations of DNMPs, an additional Na + ion was included to ensure electroneutrality of the system. A view of a typical DNMP system as simulated is shown in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…20e Water was modeled explicitly using the TIP4P-Ew model; 24 we selected this model for use in simulations because one of our long-term goals is to study protein-DNA interactions and the combination of the AMBER protein force field with the TIP4P-Ew water model is established as one of the best currently available for modeling peptide systems. 25 Na + and Cl − ions – which were added to 150 mM concentrations in order to crudely mimic physiological concentrations – were modeled using the appropriate set of parameters derived by Joung & Cheatham; 26 for simulations of DNMPs, an additional Na + ion was included to ensure electroneutrality of the system. A view of a typical DNMP system as simulated is shown in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, for smaller systems – especially short peptides – the present results suggest that a need to recalculate partial charges for the termini might be a potential factor to consider if poor agreement with experimental observables is encountered. 2 …”
Section: Discussionmentioning
confidence: 99%
“…We have derived these additional potential functions by applying the IBI method 38,39 to MD data obtained from 441 two-residue peptides reported in recent work 40 and from a further 45 MD simulations of peptide systems reported here. In all cases, we have found that the IBI procedure enables optimized potential functions to be derived that produce a high level of agreement with the probability distributions obtained from MD (see Figures 2, 3 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…This study takes as its starting point the results of extensive explicit-solvent MD simulations of all combinations of two-residue peptides (441 systems in all) that we reported recently. 40 Here, we describe the derivation and testing of bonded potential functions for backbone pseudoatoms and the additional nonbonded potential functions required to describe the conformational energetics of peptides and proteins. Tests of the extended COFFDROP force field against further MD simulations, and against experimental data on the hydrodynamic radii of intrinsically disordered proteins indicate that the resulting force field is likely to be useful for modeling proteins in a variety of scenarios.…”
Section: Introductionmentioning
confidence: 99%